Green coffee been exposure and symptoms in dock workers in Trieste (Italy) - Gasperazzo, Anna; Toffanin, Paolo; Larese Filon, Francesca (La Medicina del Lavoro, 2017)
Background: Green coffee workers can develop allergic symptoms due to green coffee beans (GCB) or to castor bean (CB) that can contaminate sacks used for the transportation. Data are limited in literature and a previous study performed in Trieste demonstrated allergic symptoms in 14.3% of dockworkers handling GCB. Objectives: To evaluate symptoms and exposure to GCB ultrafine particles in Trieste dockworkers. Methods: Workers involved in GCB sacks transportation, storage and opening were asked to fill out a questionnaire on allergic respiratory symptoms. They performed a spirometry test and an evaluation of NO exhaled breath condensate. Inhalable and respirable dust exposures were evaluated by means of personal and environmental pumps. Ultrafine particles exposure was evaluated by means of portable particles counter DISCMini. Results: Between the 40 dockworkers exposed to GCB, 28 participated in the study (70%). Five (17.9%) reported personal allergy symptoms and two workers (7.1%) reported allergic oculorhinitis during work. One subject had symptoms only with Tanzania sacks and he resulted sensitized to CB. Workplace dust evaluation demonstrated values below Threshold Limit Values, but some work tasks were associated with exposure to more than 40,000 ultrafine particles with a geometric mean size of 37.2±1.35 nm. Conclusions: Prevalence of allergic symptoms in GCB workers was low but the presence of peaks of ultrafine particles exposure suggests the need to protect workers from exposure, limiting powder dispersion, avoiding the unloading of sacks inside the container and suggesting personal protective equipment regular use (FFP3).